2000
DOI: 10.1021/jm001003p
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Immunosuppressive Activity of Novel Prodigiosin Derivatives

Abstract: Prodigiosins (Ps) represent a family of naturally occurring red pigments characterized by a common pyrrolylpyrromethene skeleton. Some members of this family have been shown to possess interesting immunosuppressive properties exerted with a novel mechanism of action, different from that of currently used drugs. In fact, Ps inhibit phosphorylation and activation of JAK-3, a cytoplasmic tyrosine kinase associated with a cell surface receptor component called common gamma-chain, which is exclusive of all IL-2 cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
112
0
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(117 citation statements)
references
References 24 publications
(26 reference statements)
0
112
0
5
Order By: Relevance
“…Consequently, prodigiosins are of interest because they might have potential clinical utility. Prodigiosins and synthetic derivatives have been shown to have potent and specific immunosuppressive activity, with novel targets clearly distinct from other drugs (D'Alessio et al, 2000;Mortellaro et al, 1999;Tsuji et al, 1990Tsuji et al, , 1992. Montaner et al (2000) showed that prodigiosin extracted from S. marcescens could induce apoptosis in haematopoietic cancer cell lines including acute T-cell leukaemia, myeloma and Burkitt's lymphoma, with little effect on non-malignant cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, prodigiosins are of interest because they might have potential clinical utility. Prodigiosins and synthetic derivatives have been shown to have potent and specific immunosuppressive activity, with novel targets clearly distinct from other drugs (D'Alessio et al, 2000;Mortellaro et al, 1999;Tsuji et al, 1990Tsuji et al, , 1992. Montaner et al (2000) showed that prodigiosin extracted from S. marcescens could induce apoptosis in haematopoietic cancer cell lines including acute T-cell leukaemia, myeloma and Burkitt's lymphoma, with little effect on non-malignant cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…31) In addition, replacement of the A-pyrrole ring with a thiophene group on synthetic prodigiosin molecule results in disappearance of the ability to promote strand-scission of supercoiled DNA in the presence of copper 32) and cytotoxicity. 33) The same effect is also achieved by attaching an electron-withdrawing substituent (acetyl group) to the 5Ј-position of the A-pyrrole ring. 25) Therefore, PG-L-1 molecule might have different structure from PG molecule at A-pyrrole ring.…”
Section: Discussionmentioning
confidence: 95%
“…[8][9][10] Cycloadditon reactions of this type are unique to isocyanides. The reaction of isocyanides with carbon-carbon double bonds tends to occur in a stepwise manner and is involves a zwitterionic intermediate the ultimate fate of which appears to be dictated by the nature of the original double bond substrate.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Using the isocyanide carbon atom for synthesis of many cyclic systems in a formal…”
Section: Introductionmentioning
confidence: 99%